As lágrimas do Menino Jesus : entre a doutrina e a poesia - Morujão, Isabel (2014)
In Portuguese religious lyrics, the Holly Infant's tears are a poetic motive with a large impact, especially since the late 16th century. Following a scanning of the main authors who have dealt with this subject, an attempt is made to outline the main semantic-theological vectors of the motive. The connections between this poetic-religious discourse and some kinds of spiritual prose (ars orandi, sermons, meditations) are then underlined, with a particular incidence on the close and interactive dialogue involving these diverse textual modes.